Penentuan Takaran Pupuk Nitrogen pada Tanaman Jagung Hibrida Berdasarkan Klorofil Meter dan Bagan Warna Daun - Efendi, Roy; Suwardi, Suwardi; Syafruddin, Syafruddin; Zubachtirodin, Zubachtirodin (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
Synchronization the amount of N nutrient needed for maize growth and the availability of indigenous N in the soil + N fertlizer, is important to obtain a high maize yield. An alternative technique to identify the N nutrient adequacy on maize is by using the chlorophyll meter or the leaf color chart (LCC). The research objective was to determine the rate and time of N fertilizer application for hybrids maize based on the content of N in the leaf as measured by chlorophyll meter and LCC. The experiments were conducted using a split plot design with three replications. The main plots were the rate of N fertilizer, namely 0, 75, 150, and 225 kg N/ha. The subplots were the corn varieties Pioneer 21 and Bisi 2. Results showed that the N fertilizer requirements for maize crops as measured using the chlorophyll meter and the LCC were positively correlated with the actual levels of N requirement. Both measurement techniques can be used to identify the N nutrient requirement for maize during the plant growth stages V12 and VT. Determination of the critical N status by grouping stages of plants with sufficient and insufficient N nutrient indicated that chlorophyll meter value was more accurate than the use of LCC. The deviation of measurements of N fertilizer requirements at plant growth stages V12 and VT using the chlorophyll meter was smaller (11.1% and 2.7%) than those using the LCC (16.1% and 8.3%). The critical N status as measured using the chlorophyll meter and the LCC at V12 was 52 units, and the BWD 4.7, whereas the critical N status at VT was 50 units using the chlorophyll meter and scale 4.4 using the LCC. The estimated N fertilizer required at V12 with maize yield target of 9-10 t/ha was the value of the chlorophyll meter <41unit or the LCC <4 with the rates of N fertilizers of 125-131 kg/ha. If the chlorophyll meter value was 42-46 units or LCC 4.0 to 4.2, the rates of N fertilizer to be applied ranged from 87-119 kg N/ha. With the value of the chlorophyll meter 47-50 units or values of LCC 4.3 to 4.5, the rate of N fertilizer required ranged from 46-78 kg N/ha.